Pedagogical Innovations and Student Voices: A Longitudinal Examination of Engagement in Elementary Schools - Sharifah Ibrahim Alghamdi (International Journal of Education Sciences, 2024)
From 2023 to 2024, this mixed-approaches longitudinal study follows students of varying ages to see how characteristics related to emotional and social development, curriculum flexibility, and innovative teaching methods affect their engagement and performance in the classroom. Educators and students are followed for one year in this study to see how educational approaches change and impact students' learning. For this study, researchers conducted a one-time survey of a sizable group of teachers and students to compile quantitative data on topics such as classroom climate, student engagement, technological resources, and the prevalence of creative pedagogy. Key aspects of child-centered learning and emotional and social development were identified through factor analysis, and patterns across time were studied through longitudinal analysis. Qualitative data was gathered through task-based classroom observations, teacher interviews, and student focus groups. Recurring themes concerning the efficacy of pedagogical approaches and the significance of social and emotional support in encouraging student engagement were uncovered via the use of thematic analysis. The study found that curricular flexibility and creative teaching methods significantly boosted students' involvement and academic performance. When paired with an environment that fosters kids' social and emotional development, this becomes much more evident. Combining quantitative and qualitative data is required to fully understand the interplay between these factors and how they affect learning results. Educators and policymakers can use the data to inform their pursuit of better teaching practices and the promotion of students' holistic development across age groups.
Keywords: 21st Century learners; Teaching methods; education technology; flexible curriculum; holistic education; student engagement